My Wartime Self: Meaning Construction in Narratives of World War II - Wiest, Julie B. (Narrative Works, 2013)
We are all storytellers. We tell stories in a variety of settings, to a variety of audiences, and for a variety of reasons. We tell structured stories about personal experiences—narratives—as a means of understanding the past, constructing identities, and communicating ourselves to others. Drawing on social psychological literature on narratives, identities, and autobiographical memories, this study examines the construction, recitation, and evaluation of 28 World War II veterans’ narratives. Findings indicate cultural influences in the ways these veterans constructed their war stories, the ways they constructed meanings about their war experiences, and the ways they constructed their identities in relation to those experiences.